Treatment patterns and safety of adjuvant therapy after chemoimmunotherapy for early-stage triplenegative breast cancer in a real-world scenario: the Neo-Real/GBECAM-0123 study - Bonadio, Renata Rodrigues da Cunha Colombo; Testa, Laura; Tavares, Monique; Assad-Suzuki, Daniele A; Rosa, Daniela Dornelles; Gagliato, Débora de Melo; Diz, Maria del Pilar Estevez; Sousa, Romualdo Barroso (Mastology, 2026)
Introduction: The KEYNOTE-522 trial established neoadjuvant pembrolizumab plus chemotherapy (P+CT) followed by adjuvant pembrolizumab as the standard of care for stage II–III triple-negative breast cancer. However, integrating this regimen with other adjuvant therapies, such as capecitabine or olaparib, remains uncertain in clinical practice. Objective: This study aimed to evaluate real-world treatment patterns and safety outcomes of adjuvant therapies following neoadjuvant P+CT. Methods: This multicentric Neo-Real/GBECAM-0123 study included triple-negative breast cancer patients treated with neoadjuvant P+CT since July 2010 across ten cancer centers. The analysis focused on treatment patterns and safety, particularly grade ≥3 adverse events (AEs). Results: Out of the 410 patients enrolled, 359 underwent surgery and 185 completed adjuvant therapy. The median age was 43 years; 69.5% had stage II and 25.8% had stage III disease. A pathologic complete response was achieved in 62.5% (n=218); among them, 85.9% continued adjuvant pembrolizumab. In breast cancer wild-type unknown patients with residual disease (n=114), 54.4% received pembrolizumab plus capecitabine (P+C), 26.3% pembrolizumab alone, and 10.5% capecitabine alone. Among breast cancer-mutated patients with residual disease (n=12), 75% received pembrolizumab plus olaparib (P+O), 16.7% P+C, and 8.3% olaparib alone. Grade ≥3 AEs rates were higher with P+C (16.3%) and P+O (14.3%) compared to pembrolizumab alone (6.3%; p=0.057). Anemia grade ≥3 occurred in 14.3% of P+O patients vs. 0% pembrolizumab alone, while diarrhea (6.1%) and hand-foot syndrome (8.2%) were more frequent with P+C. No increase in immune-related grade ≥3 AEs was observed with combinations. Conclusion: In a realworld scenario, most patients with triple-negative breast cancer continued adjuvant pembrolizumab after a pathologic complete response, while adjuvant capecitabine and adjuvant olaparib were frequently used in combination with pembrolizumab for those with residual disease. Combined adjuvant strategies showed higher rates of grade ≥3 AEs and drug discontinuations. The efficacy of the combined adjuvant strategies remains to be determined.